A systematic review of strategies to increase drinking‐water access and consumption among 0‐ to 5‐year‐olds. (28th June 2019) - Cradock, Angie L.; Poole, Mary Kathryn; Agnew, Kaylan E.; Flax, Chasmine; Plank, Kaela; Capdarest‐Arest, Nicole; Patel, Anisha I.
Summary: The objective of this study is to identify promising strategies for improving drinking‐water access and consumption among children aged 0 to 5 years. MEDLINE/PubMed, Embase, ERIC, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched in this review. Studies included peer‐reviewed, full‐text studies from high‐income countries, published in English between January 1, 2000, and January 12, 2018, that evaluated interventions to increase water access or consumption in children aged 0 to 5 years. Twenty‐five studies met inclusion criteria; 19 used an effective intervention strategy to increase water access or water consumption. Three studies addressed both water access and consumption. Frequently used strategies included policy and practice changes, increasing water access and convenience, and education, training, or social support for caregivers. Studies were of fair methodological quality (average score: 18.8 of 26) for randomized studies and of moderate quality (5.1 of 9) for non‐randomized studies. To date, few high‐quality studies with objectively measured outcomes have clearly demonstrated strategies that may influence water intake and consumption among young children aged 0 to 5 years.